Laboratory evaluation of trap color and vinegar, yeast and fruit juice lure combinations for monitoring of Zaprionus indianus (Diptera: Drosophilidae). Issue 3 (2nd July 2020) - Lasa, Rodrigo; Gschaedler-Mathis, Anne C.; Bello, Gerardo; Williams, Trevor
Abstract: Zaprionus indianus Gupta (Diptera: Drosophilidae) is a successful invasive drosophilid that is currently impacting fig production in Mexico and Brazil. Very few studies have examined the improvement of trapping strategies for this pest. Here, we compared visual responses of Z. indianus to different colors and olfactory cues. Orange and brown colored traps were among the most attractive in choice and no-choice tests, with violet and white being the least attractive colors. Orange traps with brown circles around the access holes were more attractive than uniformly orange traps. Apple cider vinegar was significantly more attractive to adults than sugar cane vinegar or grape juice but was not significantly more attractive than white wine and red wine vinegars. Captures of Z. indianus in apple cider vinegar-baited traps were not improved by the addition of grape, pineapple or apple juices, or when compared against a sucrose solution or grape juice fermented with Saccharomyces cerevisiae, or grape juice fermented with Candida tropicalis . Pairwise comparisons of Z. indianus attraction to S. cerevisiae and C. tropicalis indicated a high dependence on the growth media used. Orange traps with brown circles baited with apple cider vinegar may prove useful for monitoring this pest under field conditions.